2016
DOI: 10.1186/s13071-016-1811-z
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and dispersal routes of an invasive parasite, Fascioloides magna, in North America and Europe

Abstract: Background Fascioloides magna (Trematoda: Fasciolidae) is an important liver parasite of a wide range of free-living and domestic ruminants; it represents a remarkable species due to its large spatial distribution, invasive character, and potential to colonize new territories. The present study provides patterns of population genetic structure and admixture in F. magna across all enzootic regions in North America and natural foci in Europe, and infers migratory routes of the parasite on both continents.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Studies on the genetic diversity and differentiation between parasites are of special importance since they can expand the understanding of their distribution patterns and processes of speciation [14]. There is still limited information regarding the evolutionary history and speciation processes in S. lupi and S. vulpis , contrary to knowledge on other helminth parasites, such as Fasciola hepatica [8], Fascioloides magna [51] and Anisakis spp. [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the genetic diversity and differentiation between parasites are of special importance since they can expand the understanding of their distribution patterns and processes of speciation [14]. There is still limited information regarding the evolutionary history and speciation processes in S. lupi and S. vulpis , contrary to knowledge on other helminth parasites, such as Fasciola hepatica [8], Fascioloides magna [51] and Anisakis spp. [52].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a high genetic diversity within each host but low differentiation between populations was found in F. hepatica , with the implications of possible spread of anthelmintic resistance genes. Additionally, a migratory route of hosts infected with F. magna and a speciation foci was found in a genetic population study [51]. Spirocerca spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it may affect populations of new host species through parasite "spillover" (Iglesias et al, 2015), and also alter the success of other parasites already present in the new domain through competition for existing and new hosts (Dunn, 2009). In turn, the parasite itself may as a result of its introduction undergo evolutionary change in order to adapt to its new circumstances (e.g., Juhasova et al, 2016).…”
Section: Introduction-parasite Invasivenessmentioning
confidence: 99%
“…These polymorphic tandem repeats were previously employed in studies of the population structures of medically important human parasites (e.g., Schistosoma haematobium, Gower et al, (2011)). However, they are still strongly underutilized in studies of parasitic platyhelminths in wildlife, as only a few papers focusing on cestodes (i.e., Luo, Nie, Zhang, Yao & Wang, 2003;Štefka, Hypša & Scholz, 2009;Umhang et al, 2018;Bazsalovicsová et al, 2020) or digeneans (i.e., Criscione, Cooper & Blouin, 2006;Louhi, Karvonen, Rellstab & Jokela, 2010;Criscione, Vilas, Paniagua & Blouin, 2011;Valdivia, Criscione, Cárdenas, Durán & Oliva, 2014;Dar, Vignoles, Rondeland & Dreyfuss, 2015;Juhásová et al, 2016;Vásquez et al, 2016;van Paridon, Colwell, Goater & Gilleard, 2017;Criscione, van Paridon, Gilleard & Goater, 2020) have so far been published. The above studies have shown that microsatellites, as molecular population markers, are more discriminative than rDNA and mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies have shown that microsatellites, as molecular population markers, are more discriminative than rDNA and mtDNA. They have also demonstrated their usefulness in revealing the population genetic structure and historical migratory routes of parasites with a wide distribution range (Štefka et al, 2009;Juhásová et al, 2016;Bazsalovicsová et al, 2020), and also migratory patterns of their hosts . However, prior to our study, no population genetic studies utilizing microsatellites had been performed on monogeneans.…”
Section: Discussionmentioning
confidence: 99%